Enhanced UMTS Simulation-based Planning in Office Scenarios - Cabral, Orlando Manuel Brito (2006)
Enhanced UMTS traffic characterisation parameters have been addressed for the offices scenario. By using a system level simulator, results concerning QoS measures as packet delay, blocking and handover failure probabilities have been obtained. If the cell radius decreases and the number of BSs increases the blocking probability decreases with a linear trend. One concludes that the supported traffic and the corresponding throughput significantly increase when the cell radius decreases. However, increasing system capacity by decreasing the cell radius causes an increase in the intensity of handovers and a decrease in the throughput per BS. Hence, optimum values for the coverage distance will correspond to higher cell radius. Delay and delay variation are not a limitation.